Pituitary haemorrhage and infarction: the spectrum of disease. Issue 2 (February 2021) - Iqbal, Fizzah; Adams, William; Dimitropoulos, Ioannis; Muquit, Samiul; Flanagan, Daniel
Abstract : Background: Pituitary apoplexy is an acute syndrome of haemorrhage or infarction into the pituitary. The condition is relatively well-described. Less well-described is sub-acute presentation of the same condition. Objective: To compare the clinical presentation and natural history of subacute pituitary haemorrhage/infarction with pituitary apoplexy (acute). Method: Retrospective analysis of a consecutive cohort of 55 patients (33 with pituitary apoplexy, 22 with subacute disease) presenting to University Hospital Plymouth between 1994 and 2019. Comparison of the clinical, endocrinological and radiological features at presentation. Comparison of clinical treatment and subsequent outcomes for the two groups. Results: There were no significant differences in predisposing factors for the two groups. Acute headache was more frequent in the acute group. Chronic headache was common in both groups prior to presentation. Low sodium was more common at presentation in the acute group (11/26 vs 2/19 P = 0.02) otherwise there were no differences in endocrine deficit at presentation. A significant proportion showed an improvement in endocrine function at follow up (acute 8/31, subacute 5/21 P = 1.0). MRI characteristics were variable at presentation and follow up in both groups. Ring enhancement with contrast was more frequent in acute (14/20 vs 3/11 P = 0.03). This appearance resolved at follow up in the majority. Conclusions: Pituitary apoplexy has a characteristic and dramatic presentation. Subacute pituitary haemorrhage/infarction shows similar natural history and outcome. These conditions would appear to represent a spectrum of the same condition.